2020
DOI: 10.12659/msm.926393
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the C-Reactive Protein to Lymphocyte Ratio and Disease Severity in 108 Patients with Early COVID-19 Pneumonia from January to March 2020 in Wuhan, China

Abstract: Background The aim of this study was to determine the effect of C-reactive protein (CRP), lymphocytes (LYM), and the ratio of CRP to LYM (CRP/LYM) on assessing the prognosis of COVID-19 severity at early stages of disease. Material/Methods A total of 108 hospitalized patients diagnosed with COVID-19 in Zhongnan Hospital of Wuhan University from January 17, 2020 to March 12, 2020 were enrolled. Data of demographic parameters, clinical characteristics, laboratory indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 30 publications
5
50
0
4
Order By: Relevance
“…A surprisingly high number of papers have focused on circulating CRP levels in COVID-19 patients, with multiple lines of evidence showing the prognostic value of this biomarker [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Studies addressing the clinical usefulness of CRP have mostly reported a positive association between disease severity and baseline values.…”
Section: Crp Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…A surprisingly high number of papers have focused on circulating CRP levels in COVID-19 patients, with multiple lines of evidence showing the prognostic value of this biomarker [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Studies addressing the clinical usefulness of CRP have mostly reported a positive association between disease severity and baseline values.…”
Section: Crp Levelmentioning
confidence: 99%
“…Despite the retrospective single-center design of this study, variables with missing values were not included in the analysis, which strengthens the findings. Yang, et al [19] analyzed CRP levels in 108 COVID-19 patients to assess its effectiveness as a biomarker of disease severity. The CRP level and CRP-to-LC ratio had high prognostic value in the early disease stage.…”
Section: Crp Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, lymphopenia can be a good indicator of disease severity [ 13 ]. It was also suggested that CRP to lymphocyte ratio can be a better marker than lymphocyte count alone for assessment of the disease severity in the early stage of disease [ 14 ]. In addition, 10.6% of patients in our study presented with elevated serum amylase and lipase.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are even suggested for SARS and COVID-19 treatment to reduce inflammation (Cinatl Jr et al 2005 ; Xiang et al 2020 ). However, since high doses are recommended for acute respiratory infections, prolonged use may lead to opportunistic infections in the background of immune suppression (Klein et al 2001 ; Cinatl Jr et al 2005 ; Lossignol 2016 ; Yang et al 2020a ). Since cancer patients are in the high-risk group for COVID-19, addressing SARS-CoV-2 induced inflammation alone with high doses of glucocorticoids can lower host immunity and thus, can aggravate both cancer and virus spread and can invite other infections to occur in cancer patients (Slimano et al 2020 ; Hanna et al 2020 ; Russell et al 2020 ; Table 4 ).…”
Section: Potential Inhibitors Of Cytokine Storm In the Context Of Sarmentioning
confidence: 99%